Abstracts from the 4. Australian conference on mathematics and computers in sport, 1998 (1998)
The conference was held from 13-15 July 1998 at BOND UNIVERSITY, QUEENSLAND The fourth conference in this series was held at Bond in July under the joint directorship of Neville de Mestre and Kuldeep Kumar. There were 34 attendees and 22 papers presented. Overseas attendance included 2 from NZ, one from England and one from Canada. The conference was opened by Grant Hackett, a student at Bond and currently World and Commonwealth 1500 metres champion.